Music scenes : local, translocal and virtual - Bennett, Andy, 1963-; Peterson, Richard A. (Vanderbilt University Press, 2004)
The fascinating world of â€œmusic scenes, â€₊ where local musicians and fans explore common musical tastesand create distinctive lifestyles.